Performance of rapid diagnostic test, blood-film microscopy and PCR for the diagnosis of malaria infection among febrile children from Korogwe District, Tanzania. (December 2016) - Mahende, Coline; Ngasala, Billy; Lusingu, John; Yong, Tai-Soon; Lushino, Paminus; Lemnge, Martha; Mmbando, Bruno; Premji, Zul
Abstract Background Rapid diagnostic tests (RDT) and light microscopy are still recommended for diagnosis to guide the clinical management of malaria despite difficult challenges in rural settings. The performance of these tests may be affected by several factors, including malaria prevalence and intensity of transmission. The study evaluated the diagnostic performance of malaria RDT, light microscopy and polymerase chain reaction (PCR) in detecting malaria infections among febrile children at outpatient clinic in Korogwe District, northeastern Tanzania. Methods The study enrolled children aged 2–59 months with fever and/or history of fever in the previous 48 h attending outpatient clinics. Blood samples were collected for identification ofPlasmodium falciparum infection using histidine-rich-protein-2 (HRP-2)-based malaria RDT, light microscopy and conventional PCR. Results A total of 867 febrile patients were enrolled into the study. Malaria-positive samples were 85/867 (9.8 %, 95 % CI, 7.9–12.0 %) by RDT, 72/867 (8.3 %, 95 % CI, 6.5–10.1 %) by microscopy and 79/677 (11.7 %, 95 % CI, 9.3–14.3 %) by PCR. The performance of malaria RDT compared with microscopy results had sensitivity and positive predictive value (PPV) of 88.9 % (95 % CI, 79.3–95.1 %) and 75.3 % (95 % CI, 64.8–84.0 %), respectively. Confirmation ofP. falciparum infection with PCR analysis provided lower sensitivity and PPV of 88.6 % (95 % CI, 79.5–94.7 %) and 84.3 % (95 % CI, 74.7–91.4 %) for RDT compared to microscopy. Conclusion Diagnosis of malaria infection is still a challenge due to variation in results among diagnostic methods. HRP-2 malaria RDT and microscopy were less sensitive than PCR. Diagnostic tools with high sensitivity are required in areas of low malaria transmission.